Penerapan Sistem Pembangkit Listrik Tenaga Surya Pada Alat Pembuat Pupuk Organik Cair di Desa Banjarwaru - Zaenurrohman, Zaenurrohman; Susanti , Hera; Alimudin, Erna; Sumardiono, Arif; Santoso, Agus (Politeknik Negeri Cilacap, 2025)
The majority of the population of Banjarwaru Village are farmers. The price of fertilizer is getting higher from time to time while farmers need fertilizer for their plants. Problems arise when fertilizer shortages often occur. In addition, the type of fertilizer used is generally a type of chemical fertilizer that is not good for the human body because the substance can be carried into the food consumed. Organic fertilizer is one option to overcome this problem. This type of fertilizer is now starting to be widely available on the market, although the price is relatively expensive. The solution to this problem is that it can be done by making organic fertilizer independently. Another factor is that there is a lot of organic waste that can be processed into liquid organic fertilizer (POC). Therefore, to create a village that is independent in fertilizer, the PKM Team aims to create an organic fertilizer maker based on a PLTS electricity source and provide training in operating the tool. The method used is by making an organic liquid fertilizer maker, socializing it to residents of Banjarwaru Village, and training and demonstrating how to operate the tool.